Influences, discourse, and conceptions about engineering and gender, in the voices of FIO-UNICEN incoming students - Garcia De Cajén, Silvia; Haydée Peralta, María (LACCEI, 2025)
This paper shares the results of an analysis of the narratives collected during the Introductory Course of the Faculty of Engineering (FIO) at UNICEN, Argentina, during the years 2023/2024/2025. This survey was designed by the MIFIO group and implemented by course instructors among incoming female and male students. While it aims to examine the factors that influence the choice of engineering, the discourse they hold, and the conceptions about the relationship between engineering and gender, it also provides insight into women’s participation in scientific and technological careers. The study, promoted within FIO-UNICEN, provides revealing insights into the motivations, expectations, and stereotypes, as well as the (inequality of) opportunities that permeate scientific and technological careers. There are strong messages that challenge students, but at the same time, invite them to continue working toward more inclusive and equitable environments. The qualitative and quantitative analysis of the survey, which includes 5 open-ended questions, allows us to arrive at reflections that become relevant when proposing good practices to contribute to reducing the gender gap in engineering